2018
DOI: 10.1063/1.5028076
|View full text |Cite
|
Sign up to set email alerts
|

Customer relationship management implementation in the small and medium enterprise

Abstract: Abstract.To win the global competition and sustain the business, small and medium enterprise shall implement a reliable information technology application to support their customer data base, production and sales as well as marketing management. This paper addresses the implementation of Customer Relationship Management (CRM) in small and medium enterprise, CV. Densuko Jaya. It is a small and medium enterprises in Semarang, Central Java, Republic of Indonesia deal with rubber processing industry supply chain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Sari & Firdaus (2018) made another research of TQM implementation in SME (Small Medium Enterprise) sector in Indonesia, where they concluded that TQM implementation can improve the competitive advantage of the SME. Similarly, Nugroho & Nurcahyo (2018) also did a research in SME in Indonesia where they concluded that TQM implementation can improve the financial performance of SME.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Sari & Firdaus (2018) made another research of TQM implementation in SME (Small Medium Enterprise) sector in Indonesia, where they concluded that TQM implementation can improve the competitive advantage of the SME. Similarly, Nugroho & Nurcahyo (2018) also did a research in SME in Indonesia where they concluded that TQM implementation can improve the financial performance of SME.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Untuk memenangkan persaingan dan mempertahankan bisnis di era yang sangat kompetitif, usaha kecil dan menengah harus menerapkan teknologi yang dapat mendukung basis data pelanggan, produksi dan penjualan serta manajemen pemasaran untuk menjalin komunikasi yang baik dengan pelanggannya. Salah satu aplikasi teknologi informasi yang memungkinkan untuk usaha kecil dan menengah adalah Customer Relationship Management (CRM) [6]. CRM merupakan strategi yang dilakukan perusahaan agar tetap konsisten menjaga hubungan dengan pelanggan.…”
Section: Pendahuluanunclassified
“…This focus on customer becomes even more crucial for small and medium enterprises (SMEs) due to the presence of severe challenges in expanding their business and surviving in a competitive business market. It further helps SMEs by enabling improved business performance, enhancing productivity, promoting innovation, raising market share, reducing cost, and improving customer value (Nugroho, Suharmanto and Masugino, 2018). Since the absence of customer retention could result in huge losses for the company, the implementation of advanced technologies for assessing customer data becomes paramount.…”
Section: Introductionmentioning
confidence: 99%